Visuospatial function impairment in patients with subacute-chronic isolated frontal lobe ischemic stroke: A cross-sectional study using MoCA-Ina in a private hospital - Mary Christina Elsa; Yusak Mangara Tua Siahaan; Melania Lumenta (Romanian Journal of Neurology)
Background. Stroke is one of the leading causes of disability, resulting in both limb disability and also cognitive impairment. Cognitive impairment can occur post-stroke due to lesions in specific cortex areas. Visuospatial function, a domain of cognitive function related to visual imaging, is commonly affected by parietal lobe lesions. However, visuospatial processing also requires sustained attention, planning, and error correction, functions of the frontal lobe. There is a paucity of studies evaluating the relationship between isolated frontal lobe stroke and patients’ visuospatial function. Objective. To analyze the relationship between subacute-chronic frontal lobe ischemic stroke and visuospatial function in post-ischemic stroke patients using the MoCA-Ina. Material and methods. Patients from Siloam Karawaci General Hospital’s neurology outpatient department with ages under 65 years, Glasgow Coma Scale of 15, diagnosis of first-time stroke based on CT scan result, and ischemic lesion confined to one brain lobe were recruited using non-probability consecutive sampling for this cross-sectional study. Patients were divided into frontal lobe and non-frontal lobe stroke subgroups. Visuospatial function was assessed using MoCA-Ina and analyzed using Mann Whitney U test. Outcomes. Fifty patients were included; 25 had frontal lobe stroke, and 25 had non-frontal lobe stroke. The median visuospatial score was lower in the frontal lobe group (2, min/max = 0/4) compared to the non-frontal lobe group (3, min/max = 0/5), with a p-value of 0.044. There was no significant difference in visuospatial scores between different frontal hemisphere locations. Conclusion. Subacute-chronic frontal lobe ischemic stroke affects visuospatial function in post-ischemic stroke patients.